The role of surgery in tuberculosis management - Zaleskis, Richard (Henry Stewart Talks, 2021)
History of surgical treatment of pulmonary TB, Indications for surgical treatment of TB, Types of operations, Preoperative management, Surgical versus non-surgical treatment methods, Surgery in TB and MDR/XDR